2009
DOI: 10.1016/j.jvs.2008.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of postprocedure microemboli following retrospective quality assessment and practice improvement measures for carotid angioplasty and stenting

Abstract: Despite successful performance of 47 consecutive CAS procedures without permanent neurologic sequelae, significant reductions in periprocedural embolic events as identified via DW-MRI lesions may be achieved through implementation of quality improvement measures identified through continuous outcome analysis. The long-term neurologic benefits associated with reduced subclinical neurologic events remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…It has been shown by some investigators that omitting the arch angiogram, early heparinization, and preferential use of closed-cell stents reduced the rate of new DW-MRI lesions. 24 We believe that in our hands, an arch angiogram minimizes catheter manipulation in the arch during selective carotid cannulation and limits the particulate embolic debris.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been shown by some investigators that omitting the arch angiogram, early heparinization, and preferential use of closed-cell stents reduced the rate of new DW-MRI lesions. 24 We believe that in our hands, an arch angiogram minimizes catheter manipulation in the arch during selective carotid cannulation and limits the particulate embolic debris.…”
Section: Discussionmentioning
confidence: 91%
“…22 Monitoring of MESs by TCD has been used as a quality control method during both open and percutaneous carotid revascularization. 23,24 The objective of this study was to determine MES rates during elective CEA, carotid angioplasty, and stenting with distal embolic protection device or carotid angioplasty and stenting with flow reversal (FRS).…”
mentioning
confidence: 99%
“…In a recent systematic review, microembolic events were reported to occur in 37% of patients who underwent CAS and 10% of patients who underwent CEA [18]. Early in our experience with CAS, our institution reported a higher than expected incidence of perioperative microemboli [1], which emphasized the need for continued surveillance and changes in our practice paradigms [12]. More recently we have detailed rates of microemboli that are dramatically lower [13], with the report herein demonstrating an overall rate of microemboli at 36.8% following carotid artery stenting procedures.…”
Section: Discussionmentioning
confidence: 79%
“…More recently we have detailed rates of microemboli that are dramatically lower [13], with the report herein demonstrating an overall rate of microemboli at 36.8% following carotid artery stenting procedures. We attribute our steady decline in rates of perioperative microemboli to guidelines that we implemented at the study institution, which include the routine use of EPDs, utilization of closedcell stent systems (used in 67% of the total CAS patient population evaluated during in this study), early administration of intraoperative heparin, elimination of arch angiograms if adequate preoperative imaging is available, and the designation of specific practitioners for routine performance of CAS [12,13]. Similarly, others have observed decreased incidence of microemboli with the use of closed-cell stents, eccentric EPDs, and minimizing of supra-aortic endoluminal manipulation with catherizations and unnecessary angiograms [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation